Go!

1

2

3

4

5

6

7

8

9

0

x

y

(◻)

◻/◻

◻^{2}

◻^{◻}

√◻

∞

e

π

ln

log

lim

d/dx

d^{□}/dx^{□}

∫

∫^{◻}

>

<

>=

<=

sin

cos

tan

cot

sec

csc

asin

acos

atan

acot

asec

acsc

sinh

cosh

tanh

coth

sech

csch

asinh

acosh

atanh

acoth

asech

acsch

1

Example

$x²+3x+12=0$

2

Moving the term $x²$ to the other side of the equation with opposite sign

$12+3x=x²\left(-1\right)$

3

Subtract $12$ from both sides of the equation

$3x=x²\left(-1\right)-12$

4

Multiply both sides of the equation by $$

$x=\left(x²\left(-1\right)-12\right)\cdot \frac{1}{3}$

5

Multiply $\left(x²\left(-1\right)+-12\right)$ by $\frac{1}{3}$

$x=x²\left(-\frac{1}{3}\right)-4$

Access detailed step by step solutions to millions of problems, growing every day!